2021
DOI: 10.21203/rs.3.rs-985178/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitators, Barriers and Structural Determinants of Physical Activity in Nulliparous Pregnant Women: A Qualitative Study

Abstract: Backgrounds: Reduced physical activity in pregnant women is highly stemmed from their misconceptions and attitudes during pregnancy. This study aimed to recognize the facilitators, barriers, and structural factors that influence activity among pregnant women.Methods: This qualitative study was conducted from January to June 2020 in nulliparous pregnant women. Forty participants selected randomly from the Pounak Health Center of Tehran City, Iran, were answered open-ended questions about the obstacles that depr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Weenig & Maarleveld, 2002 also reported that time constraints can induce time stress or pressure, which constitutes a typical psychological social stress [41]. It is suggestive therefore, that time constituted being a major barrier to the performance of physical exercise for these respondents and also contributed in the inflammatory pathway that predisposed these individuals to this disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…Weenig & Maarleveld, 2002 also reported that time constraints can induce time stress or pressure, which constitutes a typical psychological social stress [41]. It is suggestive therefore, that time constituted being a major barrier to the performance of physical exercise for these respondents and also contributed in the inflammatory pathway that predisposed these individuals to this disease [7].…”
Section: Discussionmentioning
confidence: 99%